Effect of modifying β-casein by maillard reaction and genipin crosslinking on in vitro digestion of the micelles. (April 2022) - Li, Mo; Wen, Xin; Wang, Kunli; Wang, Yuxiao; Liu, Zihao; Ni, Yuanying
Abstract: β-casein (β-CN) from bovine milk has attracted increasingly interest as biocompatible, non-toxic nano-carrier for hydrophobic functional components due to molecules capable of self-assembly micellar nanostructures. In this study, Maillard reaction and genipin crosslinking were used for modifying β-CN micelles (G-CGDNs) aiming to enhance the stability and achieve a time-release capability as nano-carriers of naringenin. G-CGDNs showed a significant decrease in encapsulation efficiency of naringenin, while the controlled naringenin release properties were enhanced. In vitro studies, the effect of modification on digestibility by pepsin and trypsin were investigated using SDS-PAGE, TEM, DLS, MALDI-TOF-MS and LC-MS/MS. G-CGDNs and genipin crosslinked β-CN micelles loading naringenin (G-CNMs) were all more resistant towards action of the protease hydrolysis. Meanwhile, G-CGDNs digestive products could reassemble into uniform and large spherical micelles in the end of digestion, whereas G-CNMs and β-CN micelles loading naringenin (CNMs) were all damaged to irregular and aggregation or coalescence. Although more compact structure decreased the digestion sites of G-CGDNs to attack by pepsin and trypsin, there was slight change in the release of bioactive peptides. This research can help explore the impact of two modified approaches on β-CN micelles, which will improve stability, maintain nutritional value, and provide a delayed reaction in digestion. Graphical abstract: Image 1 Highlight: 1. Genipin crosslink decreased naringenin release rate of βCN-graft-dextran micelle 2. The micelles by genipin crosslink was more resistant towards pepsin and trypsin 3. There was slight change in release of bioactive peptides for modified β-CN micelle